Analisis Tingkat Kepuasan Aparat Desa terhadap Aplikasi Siskeudes Data Keuangan di Lolo Tana (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Assistance funds from the APBN through the West Sumba Regency APBD can be allocated to funds through the Village Financial System application. This financial system has been widely used by all village offices. However, the budget is used by the reports reported to the financial system. The purpose of the researcher is to assess the level of satisfaction with the utilization and documentation of financial resources. This study is conducted through the distribution of questionnaires to relevant respondents. Based primarily on the responses gathered from the questionnaires, the researcher employs the SPSS software as a tool for statistical data analysis. The results of the test found that all test results were valid, namely for reliable test values of 0.789, 0.779, and 0.805 through Cronbach Alpha.